OPTIMALISASI KETERAMPILAN MENGAJAR GURU MELALUI PELATIHAN KUIS INTERAKTIF BERBASIS GAMIFIKASI - Setiawaty, Rani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The problem faced by teachers of SD 2 Kesambi is that they have not utilized interactive learning media based on gamification in the learning process. Ideally, a teacher should be able to develop teaching skills, especially in providing varied learning using interesting media. This activity aims to provide training in the use of interactive quiz media based on wordwall gamification. Participants in this activity were 8 teachers of SD 2 Kesambi. The method of this training activity was in the form of socialization (lectures), practice, discussion and questions and answers. Based on the results of the implementation of the training activities, it shows that the activity has been carried out well. This success can be seen from the results of the evaluation carried out before and after the training. These results show that there is a significant increase in understanding of the creation and use of interactive quiz learning media based on wordwall gamification by teachers of SD 2 Kesambi. The understanding of participants before the training was 49% to 91% after the training. This means that previous participants did not really understand this gamification application. Then after the training, participants were able to create interactive quiz media. Thus, through training in creating interactive quiz media, teachers can improve their teaching skills.